Investigating efficiency of materials management at original equipment manufacturer (OEM) - Hassan Murshid, Zsa Zsa Nura’in; Ismail, Siti Zubaidah (Penerbit UMP, 2022)
Original Equipment Manufacturer (OEM) businesses always facing a challenge in managing the material effectively and efficiently. The aim of this is to identify, analyse and improve the Efficiency of Materials Management at Original Equipment Manufacturer (OEM) company. There are two materials management problems: stock-out and overstock, occur frequently in the OEM company. Data collection is through the observation and interviews with the top manager and other staff involved in materials management operations. Secondary data is retrieved from the related information on materials management. The collected data were categorised using IDEF0 and the development of the inventory control system used MS Excel Macro. The outcome of this research is a computerised material management system that is beneficial and essential for material management efficiency.